INTEGRASI NILAI-NILAI MODERASI DALAM PENDIDIKAN ISLAM SEBAGAI UPAYA PENCEGAHAN RADIKALISME - Madhar (AL - IBRAH, 2024)
The integration of moderation values in Islamic education is an important concern in the context of efforts to prevent radicalism. Education that prioritizes moderation can shape the character of students who are more tolerant, open-minded, and able to appreciate differences. Such education serves as a bulwark against the influence of radical ideologies that often utilize the loopholes of narrow and fanatical religious understanding. The focus of this research discusses how the conceptual study of moderation values in Islam, the influence of moderation education on the prevention of radicalism, the integration strategy of moderation values in Islamic education, and how the challenges and obstacles in the integration of moderation values in Islamic education. The results show that the integration of moderation values in Islamic education is an important step in preventing radicalism, especially among youth. Moderation values rooted in the concept of wasatiyyah in Islam include tolerance, balance, justice, and respect for diversity. Islamic education that emphasizes moderation can help shape the character of students who are more open, critical and tolerant of differences. Thus, Islamic education has a strategic role in fortifying the younger generation from the influence of radical ideologies through the dissemination of peaceful and inclusive Islamic teachings. This effort requires the support of the right curriculum, active learning methods, and character education, as well as strengthening the capacity of educators to implement moderation values effectively.